Kgp, rgpA, and rgpB DNA Vaccines Induce Antibody Responses in Experimental Peri‐Implantitis. Issue 11 (1st November 2014) - Guo, Meihua; Wang, Zhifeng; Fan, Xin; Bian, Yuanyuan; Wang, Tiantian; Zhu, Lina; Lan, Jing
Abstract : Background: Peri‐implantitis is the key factor for implant failure. This study aims to evaluate kgp, rgpA, and rgpB DNA vaccines to induce an immune response and prevent peri‐implantitis. Methods: The kgp, rgpA, and rgpB genes were amplified by polymerase chain reaction (PCR) from Porphyromonas gingivalis ( Pg ) ATCC 33277 and cloned into the pVAX1 vector. Titanium implants were placed into the mandibular bone of dogs. Three months later, the animals were divided into four groups, immunized with pVAX1‐kgp, pVAX1‐rgpA, pVAX1‐rgpB, or pVAX1. Cotton ligatures infiltrated with Pg were tied around the neck of the implants. Immunoglobulin (Ig)G and IgA antibodies were detected by enzyme‐linked immunosorbent assay before and after immunization. Results: The kgp, rgpA, and rgpB genes were successfully cloned into the pVAX1 plasmid. Animals immunized with pVAX1‐kgp and pVAX1‐rgpA showed higher titers of IgG and IgA antibodies compared to those before immunization ( P <0.05) and compared to those that were immunized with pVAX1 and pVAX1‐rgpB, whereas there were no significant differences in the animals treated with pVAX1 and pVAX1‐rgpB. Furthermore, among these, the kgp DNA vaccine was more effective. The bone losses of the groups with pVAX1‐kgp and pVAX1‐rgpA were significantly attenuated. Conclusion: pVAX1‐kgp and pVAX1‐rgpA DNA vaccines enhanced immunity responses and significantly retarded bone loss in experimental peri‐implantitis animal models, whereas pVAX1‐rgpB was ineffective.